2021
DOI: 10.5194/cp-17-615-2021
|View full text |Cite
|
Sign up to set email alerts
|

Simulated stability of the Atlantic Meridional Overturning Circulation during the Last Glacial Maximum

Abstract: Abstract. The response of the Atlantic Meridional Overturning Circulation (AMOC) to freshwater perturbations critically depends on its mean state. Large swaths of icebergs melting in the North Atlantic during the last deglaciation constituted such perturbations and can, thus, provide important constraints on the stability of the AMOC. However, the mean AMOC state during the Last Glacial Maximum (LGM), preceding the rapid disintegration of the ice sheets during the deglaciation, as well as its response to these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Second, we investigated the response of the noble gases to the colder climate of the LGM. The applied boundary conditions for the LGM are described in detail by Pöppelmeier et al (2021) and include changes in orbital and To assess the impact of even colder temperatures on the noble gases, we performed further experiments with additional top-of-the-atmosphere radiative forcing between −0.5 and −1.5 W/m 2 . The effect of different saturation anomalies on the atmospheric noble gas ratios under LGM boundary conditions was investigated by changing the residual air-sea gas exchange under sea-ice (as for the tuning of the PI state) in sensitivity experiments.…”
Section: Sensitivity Experiments and Lgm Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we investigated the response of the noble gases to the colder climate of the LGM. The applied boundary conditions for the LGM are described in detail by Pöppelmeier et al (2021) and include changes in orbital and To assess the impact of even colder temperatures on the noble gases, we performed further experiments with additional top-of-the-atmosphere radiative forcing between −0.5 and −1.5 W/m 2 . The effect of different saturation anomalies on the atmospheric noble gas ratios under LGM boundary conditions was investigated by changing the residual air-sea gas exchange under sea-ice (as for the tuning of the PI state) in sensitivity experiments.…”
Section: Sensitivity Experiments and Lgm Simulationsmentioning
confidence: 99%
“…Next to overturning circulation and sea-ice an additional process is important at the LGM in determining the change in noble gas saturation anomalies relative to PI. The massive continental ice-sheets caused average surface wind speeds at the northern high-latitudes to increase (Muglia & Schmittner, 2015) (see Figure S4 in Supporting Information S1 and Pöppelmeier et al (2021) for details on the implementation), which also increases gas transfer velocities in the model. Decreasing saturation due to larger sea-ice extent (Figures S2 and S3 in Supporting Information S1) and increasing saturation as a result of a more sluggish ocean circulation and increased gas transfer velocities can partly compensate.…”
Section: Simulated Noble Gases and Mot At The Lgmmentioning
confidence: 99%
“…Finally, we should mention that not all models show the same features of the hysteresis as our model (Muglia et al., 2018; Pöppelmeier et al., 2021; Schmittner et al., 2002). Although our findings were confirmed in two simulations, model dependency should be considered.…”
Section: Discussionmentioning
confidence: 51%
“…This study suggested that the contributions of the Nd sources are ∼ 60 % boundary/benthic source, ∼ 32 % riverine source, and ∼ 9 % dust; however, the coarse resolution of this model limits its ability to sufficiently resolve the processes affecting the Nd oceanic cycle. Later, the same authors investigated the evolution of the AMOC as it responds to freshwater perturbations under improved LGM boundary conditions in the Bern3D intermediate complexity model (Pöppelmeier et al, 2021). Pasquier et al (2022) presented the first inverse model of the global marine biogeochemical cycle of Nd using the Global Neodymium Ocean Model (GNOM) v1.0.…”
Section: Introductionmentioning
confidence: 99%